Increase Student Learning Activities by Using A Problem-Based Learning Model in Legum Technology Lecture Materials - Almira Ulimaz; Jesi Yardani; Dewi Amelia Widiyastuti (research, training and philanthropy institution Natural Aceh, 2023)
Student learning activities can be measured by how active students are while studying. A student-centered learning model is needed, especially for courses with no practicum, such as legum technology material, to make the classroom atmosphere more varied. Therefore, this study aims to increase student learning activities using a problem-based learning model in legum technology lecture materials. This research is a class action study conducted in 2 cycles, each consisting of 2 meetings. The research subject comprised 20 students majoring in Agricultural Industrial Technology, Agro-industrial Study Program. The data collection techniques include preserving student learning activities using a problem-based learning model. The results showed that the students learning activity increased with an average per cycle in cycle I of 2.14 and was included in the